Cj1388 Is a RidA Homolog and Is Required for Flagella Biosynthesis and/or Function in Campylobacter jejuni - Irons, Jessica; Sacher, Jessica C.; Szymanski, Christine M.; Downs, Diana M. (Frontiers in Microbiology, 2019)
Campylobacter jejuni is the leading bacterial cause of acute gastroenteritis worldwide and thus significant to public health. C. jejuni primarily lives in the gastrointestinal tracts of poultry and can contaminate meat during processing. Despite a small genome, the metabolic plasticity of C. jejuni allows proliferation in chicken ceca and mammalian host intestines, and survival in environments with a variety of temperatures, pH, osmotic conditions, and nutrient availabilities. The exact mechanism of C. jejuni infection is unknown, however, virulence requires motility. Our data suggest the C. jejuni RidA homolog, Cj1388, plays a role in flagellar biosynthesis, regulation, structure, and/or function and, as such is expected to influence virulence of the organism. Mutants lacking cj1388 have defects in motility, autoagglutination, and phage infectivity under the conditions tested. Comparison to the RidA paradigm from Salmonella enterica indicates the phenotypes of the C. jejuni cj1388 mutant are likely due to the inhibition of one or more pyridoxal 5′-phosphate-dependent enzymes by the reactive enamine 2-aminoacrylate.